PERGULATAN PEMAKNAAN PASAL 2 DAN 3 UUPTPK - Rifkiyati Bachri (Jurnal Yudisial, 2011)
ABSTRACTCourt decision No. 2060/Pid.B/2006/PN.Jak.Sel, in general, has complied with the substantive and procedural rules contained in the statutory provisions. Unfortunately, the judges do not dig deeper into the legal facts revealed at trial. The judges did not seem so knowledgeable about the prosecutor's indictment, particularly regarding the notions of Articles 2 and 3 of Law on Criminal Act of Corruption Eradication and less explore and understand the values that exist in society, especially people's desire to eradicate corruption in order to provide a proportionate decision. The impact is the values of justice become less reflected in the decision. The author of this article also criticizes the formulation of prosecutor's indictment.Keywords: corruption, statutory provisions, indictment formulation ABSTRACTPutusan hakim Nomor 2060/Pid.B/2006/PN.Jak.Sel, secara umum tunduk pada subtansi dan prosedur hukum yang tertuang dalam pasal-pasal. Namun sayang, hakim perlu lebih mendalami fakta hukum sehingga tidak hanya berdasarkan pengetahuan sebagaimana tertuang dalam dakwaan jaksa semata, khususnya pasal 2 dan pasal 3 UU tentang Pemberantasan Tindak Pidana Korupsi. Untuk itu, seharusnya hakim melakukan eksplorasi lebih mendalam seperti dalam nilai-nilai di masyarakat sebelum menuangkan dalam putusan sehingga menghasilkan putusan yang lebih proporsional sehingga lebih memperlihatkan nilai keadilan. Dalam tulisan ini, penulis juga mengkritisi formulasi dakwaan jaksa.Kata kunci: korupsi, pasal-pasal undang-undang, formulasai dakwaaan